2013
DOI: 10.1177/1355819613492717
|View full text |Cite
|
Sign up to set email alerts
|

Teleconsultations reduce greenhouse gas emissions

Abstract: The availability of remote care services can significantly reduce road travel and associated emissions. At a time when many countries are committed to reducing their carbon footprint, it is desirable to explore how these reductions could be incorporated into technology assessments and economic evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 9 publications
0
39
0
2
Order By: Relevance
“…Similarly, Oliviera et al . found that the use of an emerging video consultation technology, teleconsultation (or telehealth), decreased the environmental impact of care delivery. Research‐proven clinical utility (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Oliviera et al . found that the use of an emerging video consultation technology, teleconsultation (or telehealth), decreased the environmental impact of care delivery. Research‐proven clinical utility (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The use of electronic health records (EHRs) have been shown to reduce both the environmental impact of healthcare delivery and, when computerized physician order entry (CPOE) is included, mortality (31,32). Similarly, Oliviera et al (11) found that the use of an emerging video consultation technology, teleconsultation (or telehealth), decreased the environmental impact of care delivery. Research-proven clinical utility (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…10 In one of Portugal's states, teleconsultations provided in fields of neurology, dermatology, rehabilitation, and general surgery led to a 455-ton reduction in greenhouse gas emissions of vehicles. 11 The rehabilitation department at the University of Sweden, showed that replacing face-to-face consultation with telemedicine reduced carbon dioxide emission 40 to70 times less. 12 In conclusion, all countries (especially developing countries which are more vulnerable to climate change) can benefit from the environmental advantages of telemedicine which help reduce the destructive effects of global warming.…”
Section: Dear Editormentioning
confidence: 99%
“…The use of information communications technology (ICT) solutions to drive sustainability and deliver business value through cost savings and enhanced value for employees is recognized across telecommunications companies and the wider ICT sector (Falch, 2012;Kitou & Horvath, 2003;Oliveira, Barlow, Gonçalves, & Bayer, 2013;Poom, Orru, & Ahas, 2017;Ruth, 2011;Zhu & Mason, 2014). Workforce productivity is also a beneficiary from implementing video conferencing (VC).…”
Section: Introductionmentioning
confidence: 99%